(untitled) (International Journal of Architecture and Urbanism, 2024)
The author’s project of choice is an educational and leisure center housed in the former Deli Tobacco Hospital. Deli Tobacco General Hospital on Putri Hijau Street, Medan, North Sumatra. is a hospital that was founded in 1908 with the name Veregnide Deli Maatschapy Hospital. This hospital was founded to anticipate the high death rate of plantation workers at that time. The plantation workers are said to be attacked by diseases that are often found in tropical areas, such as beriberi and malaria. And now this building has been closed by PT Perkebunan Nusantara II since January 2012. Co-working spaces, libraries, museums, workshop areas, shops, restaurants, and cafÃ©s are all included in the design area’s scope. Worship spaces, parks, and playground areas are included as supporting services. The author used tropical architecture in both indoor and outdoor areas when creating this project to address the issues that arose. In and of itself, tropical architecture considers the local climate. It is envisaged that by applying the idea of Tropical Architecture to the project, the author will be able to create architectural solutions that will make users of the Edu-recreational Center more comfortable. The way the area between the internal and outdoor spaces is arranged and laid out subsequently demonstrates how this tropical architecture is being applied.